Perancangan Sistem Informasi Penjualan dan Stok dengan Dasboard Analitik untuk Mendukung Pengambilan Keputusan - Intan Royan Dini; Muji Sukur (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Most traders in traditional markets still record sales transactions and inventory manually, resulting in inaccurate data, difficulties in monitoring stock levels, and delays in business decision-making. This study aims to design and develop a desktop-based sales and inventory information system equipped with an analytical dashboard to assist store owners in recording transactions, managing inventory, and visually analyzing sales data. The research employed the Research and Development (R&D) method using the System Development Life Cycle (SDLC) with a Prototyping approach, while the system was designed using the Object-Oriented Design (OOD) approach modeled with Unified Modeling Language (UML), including use case diagrams, activity diagrams, sequence diagrams, and class diagrams. The system was developed using PHP, HTML, CSS, and JavaScript, with MySQL as the database management system. The results of Black Box Testing conducted on 14 test scenarios indicated that all system features, including transaction recording, inventory management, and analytical dashboard visualization, functioned according to user requirements. The developed system enables store owners to monitor sales performance and inventory levels in real time and supports faster, more accurate, and data-driven business decision-making.